PENANAMAN MANGROVE SEBAGAI BENTUK KEPEDULIAN STIA MATARAM DI TAMAN NASIONAL GILI PETAGAN SAMBELIA, LOMBOK TIMUR - Basuki Srihermanto; Dewi Rispawati; Iswan Iswan; Mey Susanti AS; Nia Kurniati (JURNAL PENGABDIAN MANDIRI, 2022)
This community service activity is aimed at empowering the capacity of higher education institutions in an effort to increase the community's ability to utilize knowledge to carry out Mangrove reforestation to prevent seawater abrasion and preserve the coastal environment and aims at coastal conservation. This service activity was carried out by representatives of STIA Mataram lecturers together with Panca Marga Youth activists in the NTB region and community members around Gili Petagan Sambelia National Park, East Lombok. The method used is counseling and direct action in the form of planting Mangrove seedlings at the planting site. From the results of this community service, a stretch of Mangrove seedlings that have been planted neatly filled the coast of Gili Petagan Sambelia National Park - East Lombok, it is hoped that later this Mangrove forest can withstand the waves so as to prevent abrasion. Given the importance of this community service because it can provide support and guidance for the community who will take similar actions in the future, it is hoped that this service activity can be carried out continuously